Respuesta :
Hello there!
Answer: ⇒⇒⇒ [tex]a=\frac{1}{2}[/tex]
_____________________________________________________________
Step-by-step explanation:
First expand.
[tex]\frac{2}{3}(a+6)-5=\frac{2}{3}a-1[/tex]
[tex]\frac{-1}{6}-a=-\frac{1}{6}-a[/tex]
[tex]\frac{2}{3}a-1=-\frac{1}{6}-a[/tex]
Add by 1 from both sides of equation.
[tex]\frac{2}{3}a-1+1=-\frac{1}{6}-a+1[/tex]
Simplify.
[tex]\frac{2}{3}a=-a+\frac{5}{6}[/tex]
Add by a from both sides of equation.
[tex]\frac{2}{3}a+a=-a+\frac{5}{6}+a[/tex]
Simplify.
[tex]\frac{5}{3}a=\frac{5}{6}[/tex]
Multiply by 3 from both sides of equation.
[tex]3*\frac{5}{3}a=\frac{5*3}{6}[/tex]
Simplify.
[tex]5a=\frac{5}{2}[/tex]
Then you divide by 5 from both sides of equation.
[tex]\frac{5a}5y}=\frac{5}{2}/5[/tex]
Simplify it should be the correct answer.
[tex]a=\frac{1}{2}[/tex]
___________________________________________________________
Hope this helps!
Thank you for posting your question at here on brainly.
Have a great day!
-Charlie
___________________________________________________________